The Effect of Self-Healing Microorganism-Encapsulating Concrete on Enhancing Concrete Compressive Strength - Ming Ta CHEN; Hui Yi LIN (Medžiagotyra, 2023)
Investigating microbially induced calcite precipitation (MICP) of concrete in bacillus and the durability of crack-filled repair structures were the goals of this work. The purpose of this study was to investigate the self-healing effect of concrete in bacillus and the strength of crack-filled repair structures. The characteristics of calcium carbonate particles and the performance of those penetrating cement were observed using optical microscopy. The cement block pressure test was used to study the factors affecting the healing rate of concrete materials mixed with microorganisms. The results showed that the microorganisms had good microscopic morphology. Microbial mixed soil had good compression resistance, and the ability to play a repairing role in mixed soil composite materials was that organisms could be attached to the concrete tightly. The main fracture behavior of the mixed soil was a small-hole rupture, while no macroscopic damage or large-pore ruptures were observed in the mixed soil matrix. Sporosarcina pasteurii exhibited better potential than Bacillus subtilis and could act as a self-healing agent in the concrete. The test results proved that S. pasteurii produced a colloidal adhesive to fill and repair cracks. The study designed concrete of different densities to create cubes having different compressive strengths, water permeability, and water absorption to further observe the ability of Bacillus to fill the cracks and prevent water penetration. The results showed a 60 % increase in the compressive strength of the coarse aggregate experimental sample and a 36 % decrease in the compressive strength of the fine aggregate experimental sample, relative to the same properties in the control sterile sample. Samples indicating the use of bacteria in the aggregate were denser and less porous. It was proven that the use of microorganisms could achieve self-healing ability in concrete materials, fill up pores, and establish functional effects.